2000
DOI: 10.1007/s00232001067
|View full text |Cite
|
Sign up to set email alerts
|

K+ Secretion in Strial Marginal Cells is Stimulated via β1-Adrenergic Receptors but not via β2-Adrenergic or Vasopressin Receptors

Abstract: Pharmacologic tools were used to identify receptors in functional studies by measuring either transepithelial current (I(sc)) in strial marginal cells (SMC) or cAMP production in stria vascularis (SV). Further, receptors were identified in SV as transcripts by cloning and sequencing of reverse-transcriptase polymerase chain reaction (RT-PCR) products. Experiments were performed using tissues isolated from gerbils unless specified otherwise. I(sc) under control conditions was 1090 +/- 21 microA/cm(2) (n = 213) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Evidence is emerging that supports the concept that noradrenaline accelerates K + cycling in the cochlea and the vestibular labyrinth. Noradrenaline stimulates the rate of K + secretion in strial marginal cells (Sunose et al 1997; Wangemann et al 2000). Further, outer hair cells appear to contain β 1 ‐adrenergic receptors and cAMP has been shown to stimulate the basolateral channels including the K + channel Kcnq4 (Jagger & Ashmore, 1999).…”
Section: Regulation Of K+ Cyclingmentioning
confidence: 99%
“…Evidence is emerging that supports the concept that noradrenaline accelerates K + cycling in the cochlea and the vestibular labyrinth. Noradrenaline stimulates the rate of K + secretion in strial marginal cells (Sunose et al 1997; Wangemann et al 2000). Further, outer hair cells appear to contain β 1 ‐adrenergic receptors and cAMP has been shown to stimulate the basolateral channels including the K + channel Kcnq4 (Jagger & Ashmore, 1999).…”
Section: Regulation Of K+ Cyclingmentioning
confidence: 99%
“…These K + transport pathways may be regulated by receptors that couple to G proteins. Several studies have shown the presence of G protein‐coupled receptors in the lateral wall of the cochlea (Wangemann et al. 2000, 2001; Schimanski et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of components of G protein‐mediated signal transduction pathways in the lateral wall of the mammalian cochlea. The presence of G protein‐coupled adrenergic (Wangemann et al. 2000; Schimanski et al.…”
Section: Discussionmentioning
confidence: 99%
“…G protein‐coupled receptors may regulate these K + transport pathways in the lateral cochlear wall. Several studies have shown the presence of G protein‐coupled receptors in the lateral wall of the cochlea (Wangemann et al. 2000, 2001; Schimanski et al.…”
Section: Introductionmentioning
confidence: 99%